TEKNOLOGI HEMAT ENERGI UNTUK PRODUKSI - MULJANI, SRIE (Jurnal Teknik Kimia, 2008)
The aim of this study is to calculate energy consumption at ectractive distillation process with saltsand solvent mixture as entrainer to produce fuel grade alcohol (>99.8%w). This process used twocolumn, the main exctractive column and the recovery column. A substantial reduction in the energyconsumption, compared with conventional process, was predicted by using ethylene glycol and salts isNaCl, K2CO3 and CaCl2  2CO3 : 0.05 g/ml or CaCl2  Key words : fuel grade alcohol, extractive distillation, solvent mixture0.75 g/ml or NaCl : 0.13 g/ml, at reflux ratio 1.5.as entrainer. Solvent and feed volum ratio (S/F) are varied in the range 0.3 – 1.4 , concentration salts in solvent are varied in the range 0.03 – 0.55 g salt / ml solvent and refluxratio 0.5 – 2.5. The results show that high S/F ratios increase the energy consumption, temperature ofthe solvent has important effect on distillate composition and energy consumption, this effect dependson the reflux ratio. Effect of salts show that when salts concentration increases, distillate compositionand energy consumption also increase. For distillate composition > 99.8%w, the lower energyconsumption Q = 821 KJ/kg and number of stage 36 (35% lower than conventional process) reachedin S/F ratio 0.9, K